STUDI TENTANG PELAKSANAAN PEMBELAJARAN BATIK TULIS di SMK NEGERI 8 PADANG - Achmad Chairullah, Dra. Ernis, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this study was to describe methods, media, technigues forimplementing learning batik at the Negeri 8 Padang Vocational High Scool. This type of research is descriptive research with qualitative methods. Data analysis in this study was carried out by data reduction, data presentation, data conclusion. Batik written is one of the batik technigues that has high values of creativity in designing have not been mastered by students, the batik process (Batik) will not carried out properly. In making batik, expertise and experience, precision, patienc, and a long time are needed.Keyword: Written batik; Implementation of learning